Evaluation of volatile safety in children's play mats based on non-targeted screening and risk prioritization - Shuang Liang; Haoyang Shi; Yinhui Yang; Qing Zhang; Zhijuan Wang; Qing Lv (Ecotoxicology and Environmental Safety)
Given the widespread use of play mats and their close contact with children, it is crucial to identify potential chemical hazards associated with these products. In this study, 34 play mats, comprising four materials (3 EPE, 15 XPE, 5 PVC, 11 EVA), were subjected to non-targeted screening based on headspace gas chromatography-Orbitrap high-resolution mass spectrometry (HS-GC-Orbitrap HRMS), which screened out 71 volatile substances. The 20 significantly different substances were recognized by partial least squares discriminant analysis (PLS-DA), while the characteristic substances in each type of play mat were determined through clustering heat map and Venn diagram. To facilitate the rapid identification of high-risk substances, a risk scoring scheme was developed, taking into account detection rates, average peak areas, and substance hazardousness. The substances were then ranked based on their total risk scores. The distribution of peak areas for the top 14 high-risk substances, including α-methylstyrene, formamide, and toluene, in products was detailed, highlighting the need for further attention to these chemicals. Overall, the study found the volatile chemical safety of the four play mat types to be in the order of EPE > XPE > PVC > EVA. The differentiation analysis and risk scoring scheme proposed in this paper provide significant insights for the efficient regulation and quality improvement of play mats and other products.